Application of Cooperative Learning Model with Flash Card Media to Improve Student Learning Outcomes at SDN Sugihmas in Indonesian Language Learning - Windha Yunanti (Prosiding University Research Colloquium, 2021)
The purpose of this study was to find out the effect of using the Cooperative Learningmodel with Flash Card as a means of increasing student concentration and learningoutcomes at SD Negeri Sugihmas in the Covid-19 pandemic era. This research usesClassroom Action Research (CAR) with a qualitative approach. A total of 6 students wereselected in this study using posttest techniques. Data collection techniques are studentreport cards and posttest scores with the Cooperative Learning model using Flash Card asa tool. Based on the results of data analysis, it can be concluded that using the CooperativeLearning model with Flash Card aids can increase concentration so that student learningoutcomes increase.